Strategi Pemasaran Produk Asuransi Syariah - Arini Lestari; Nuri Aslami (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2022)
The purpose of this essay is to learn about the marketing plans and techniques required by Islamic insurance companies to grow their business. In the marketing process, an important plan must be implemented, with the main goal of the company being a broad market reach. So, before entering the market, a strategy is needed that details all the plans that have been prepared, is complete and integrated, and ensures that the company's main objectives can be met through implementing the right approach. Keywords : Strategy, Marketing, Islamic Insurance